Hydrogen storage : effect of catalysts on hydrogen desorption/ absorption of Li-N-H and Li-Al-N-H systems - Somporn Thipmongkolsilp (Chulalongkorn University, 2014)
Thesis (M.S.) -- Chulalongkorn University, 2007